Our Early Experience in Surgical and Clinical Outcome on Endoscopic Cubital Tunnel Release: A Preliminary Result. (31st July 2011) - Barlaan, Philip Ian; Ip, Josephine Wing-Yuk
Abstract : Cubital tunnel syndrome is one of the common upper extremity problem encountered. A mild syndrome can be often treated without surgery, but a failure of conservative treatment with constant symptoms or muscle atrophy and weakness requires surgical intervention. Despite the fact that is the second most common nerve entrapment in the upper limb, there is no accepted gold standard in the surgical management. But with the new technique in minimally invasive surgery and available endoscope, it addresses all potential compression sites with good visualisation but with small surgical exposure. The procedure is safe and reliable way to address this problem.